Protected Hematite Nanorod Arrays with Molecular Complex Co‐Catalyst for Efficient and Stable Photoelectrochemical Water Oxidation. Issue 15 (21st December 2018) - Chen, Xiangyan; Fu, Yanming; Kong, Tingting; Shang, Yi; Niu, Fujun; Diao, Zhidan; Shen, Shaohua
Abstract : Herein, a hybrid structure of hematite (α‐Fe2 O3 ) nanorod arrays is designed, with surface catalyzed by Co molecular complex (Co(dca)2, dca: dicyanamide) and then protected by TiO2 thin overlayer, for efficient and stable photoelectrochemical (PEC) water oxidation. The obtained α‐Fe2 O3 /Co(dca)2 /TiO2 hybrid nanorod arrays show much improved and stabilized PEC performance as compared to the pristine, and even the Co(dca)2 or TiO2 modified α‐Fe2 O3, with a photocurrent density of 0.35 mA cm –2 obtained at 1.23 V vs. reversible hydrogen electrode (RHE), and an incident photon‐to‐current conversion efficiency (IPCE) reaching 16 % at 400 nm at 1.6 V vs. RHE. It has been demonstrated that the adsorbed Co(dca)2 molecular complex could effectively promote the interface charge transfer process and accelerate the water oxidation reaction kinetics, meanwhile the atomic layer deposited TiO2 overlayer could passivate the surface defects of α‐Fe2 O3 and suppress the surface charge carrier recombination. Moreover, the TiO2 overlayer could effectively protect Co(dca)2 from detaching from the α‐Fe2 O3 surface and thus stabilize the PEC activity for water oxidation reaction. The present study provides some available thoughts and methods for rational design of highly efficient photoelectrodes for water splitting from the perspective of the surface and interface engineered charge carrier transfer and water oxidation processes. Abstract : The hybrid structured α‐Fe2 O3 /Co(dca)2 /TiO2 photoanode has been designed, with surface catalyzed by Co molecular complex (Co(dca)2, dca: dicyanamide) and then protected by TiO2 thin overlayer, for efficient and stable photoelectrochemical (PEC) water oxidation. This study provids some valuable guidelines to synergistically engineer the interface charge transfer and surface water oxidation processes for efficient PEC water splitting.